Undergraduate Students’ English Pronunciation Anxiety (EPA) In Pronunciation Class at English Education Department Wiralodra University - Wati, Atikah; Efendi, Nasori; Anggrarini, Natalia; Fauziah, Ade fitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
One of the difficulties faced by non-native speakers when learning English is pronouncing sounds or words. In this case, there are many kinds of factors or problems. One of them is the feeling of anxiety when speaking English. One of them is English pronunciation anxiety. The purpose of this study is to determine the level of English Pronunciation Anxiety (EPA) of undergraduate students. The second is to determine the indicators of English Pronunciation Anxiety (EPA) of undergraduate students in pronunciation classes. This study used qualitative method and case study as a research design. The participation of this study of second-semester students in the 2022/2023 academic year, with 18 students. Overall, The researcher examined students' anxiety levels in English pronunciation, identifying two levels: